2006
DOI: 10.3844/ajassp.2006.1859.1863
|View full text |Cite
|
Sign up to set email alerts
|

Crystallisation and Melting Behavior of Methyl Esters of Palm Oil

Abstract: The methyl esters of palm oil, which consists of saturated and unsaturated esters (0.6 to 95.9% unsaturation) of the C12 to C18 fatty acids, solidify at the two temperature ranges, -52 to -45°C and -24 to 21°C, when the esters are cooled. When the esters are heated, they melt at two distinct temperatures, -25 and -33°C and a broad peak at -9 to 28°C. The heating thermograms also showed an exothermic crystallisation peak in between two endothermic melting peaks, indicating the occurrence of re-crystallisation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…This behavior could be related to the fact that the APO has about 50% of unsaturated fatty acids composition, while HOPO has around 65%. In fact, unsaturated compounds present lower melting points than saturated ones [28,32,34,35].…”
Section: Thermal Analysis Of the Oilsmentioning
confidence: 99%
“…This behavior could be related to the fact that the APO has about 50% of unsaturated fatty acids composition, while HOPO has around 65%. In fact, unsaturated compounds present lower melting points than saturated ones [28,32,34,35].…”
Section: Thermal Analysis Of the Oilsmentioning
confidence: 99%
“…However, for blends of saturated and unsaturated FAEEs the exact value of the COT is difficult to predict. A previous study reported that the position of the first crystallization peak depends very much on the content of saturated methyl esters. As the percentage of saturated methyl esters decreases, the crystallization temperature of the first exothermic peak also decreases accordingly.…”
Section: Results and Discussionmentioning
confidence: 96%
“…The process was repeated twice to verify repeatability. The rate of temperature was chosen as 5 °C/min following previous studies in FAMEs which reported a good combination of resolution characteristics and timeliness. ,, Figure shows the DSC curve obtained with the analysis of the palm biodiesel and how the COT is chosen.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of triglycerides, the variation in the composition of fatty acids strongly contribute to the formation of different crystalline forms (Hagemann et al, 1972; Sharma et al, 2009). Foon et al (2006) reported a detailed study of the influence of the fatty acid chain of the methyl ester of palm oil and found that the increase in the percentage of saturated fatty acids shifts the values of the melting points to higher and positive temperatures. Angulo et al (2018) found for the TMP ester with fish residue oil the p.p.…”
Section: Resultsmentioning
confidence: 99%